Scoliosis and Spinal Disorders - Grivas, Theodoros B.; Samartzis, Dino
Scoliosis and Spinal Disorders is an open access, multidisciplinary journal that encompasses all aspects of research on prevention, diagnosis, treatment, outcomes and cost-analyses of conservative and surgical management of all spinal deformities and disorders. Both clinical and basic science reports form the cornerstone of the journal in its endeavour to provide original, primary studies as well as narrative/systematic reviews and meta-analyses to the academic community and beyond. Scoliosis and Spinal Disorders aims to provide an integrated and balanced view of cutting-edge spine research to further enhance effective collaboration among clinical spine specialists and scientists, and to ultimately improve patient outcomes based on an evidence-based spine care approach.